2017
DOI: 10.1073/pnas.1706831114
|View full text |Cite
|
Sign up to set email alerts
|

Clipping of arginine-methylated histone tails by JMJD5 and JMJD7

Abstract: Two of the unsolved, important questions about epigenetics are: do histone arginine demethylases exist, and is the removal of histone tails by proteolysis a major epigenetic modification process? Here, we report that two orphan Jumonji C domain (JmjC)-containing proteins, JMJD5 and JMJD7, have divalent cationdependent protease activities that preferentially cleave the tails of histones 2, 3, or 4 containing methylated arginines. After the initial specific cleavage, JMJD5 and JMJD7, acting as aminopeptidases, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 60 publications
7
68
0
Order By: Relevance
“…Recent studies have proposed aminopeptidase activity for JMJD5 on histone tails containing methylated arginines 26 or N ε -monomethyl-lysines 27 . While all of our 'productive' complexes (1/A, 3 and 4) are consistent with those reported for other JmjC-hydroxylases in terms of the relationship between the active site metal and the oxidised C–H bond 41 , 42 , neither the 'productive' nor the 'non-productive' complex structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have proposed aminopeptidase activity for JMJD5 on histone tails containing methylated arginines 26 or N ε -monomethyl-lysines 27 . While all of our 'productive' complexes (1/A, 3 and 4) are consistent with those reported for other JmjC-hydroxylases in terms of the relationship between the active site metal and the oxidised C–H bond 41 , 42 , neither the 'productive' nor the 'non-productive' complex structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although there is precedent for 2OG -oxygenases being part of multi-function proteins and for the presence of the DSBH in hydrolytic enzymes 42 , our evidence is that JMJD5 is a hydroxylase rather than a hydrolase; we observed no clear evidence for JMJD5-catalysed hydrolysis of the peptides we tested (within limits of detection). Thus, it is possible that the reported histone aminopeptidase activity of JMJD5 26 , 27 requires factors other than the catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we cannot rule out that histone H3 clipping occurs in the chromatin context: This would require the targeting of the histone H3 protease to specific genomic regions, which can be addressed upon protease identification. Thus far, diverse families of proteases have been implied in histone H3 clipping, including cathepsin L-type cysteine proteases [20], tryptase [22], glutamate dehydrogenase [29], Jumonji C domain (JmjC)-containing proteins, JMJD5 and JMJD7 [30], and an unidentified yeast enzyme that has intrinsic aminopeptidase and endopeptidase activity [21]. Interestingly, Duncan et al [20] reported that covalent histone modifications modulate cathepsin L activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is essential to understand how paused Pol II is regulated in higher eukaryotes, which remains elusive to this day. In recent years, we fortuitously found that a group of orphan family members of Jumonji domain containing protein family, including JMJD5, JMJD6, and JMJD7, may work together with the super elongation complex to play critical roles in the release of paused Pol II 10‐13 (Liu et al, unpublished). The pausing of RNA Pol II at promoter regions is a unique transcription regulation mechanism seen in higher eukaryotes 48‐54 .…”
Section: Jmjd5 and Jmjd7 Cleave Arginine Methylate Histone Tails To Gmentioning
confidence: 99%